PENGARUH PROFITABILITAS, SIZE DAN DIVIDEND PAYOUT RATIO TERHADAP PRAKTIK PERATAAN LABA - Mellisa Afriliana (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2018)
The purpose of this study was to analyze the influence of profitability, size and dividend payout ratio toward income smoothing. The sample consists of manufacturing companies listed in Indonesia Stock Exchange during the period 2010-2012. This research was conducted by using a secondary data. The sampling technique conducted by the purposive sampling method. The method used to analyze is using binary logistic regression for hypothesis test, -2 Log Likelihood table for Overall model fit, Hosmer and Lemeshow’s Test for suitable regression model, classification table for accurate model test. The results of this study is profitability proxied by return on assets (ROA), net profit margin (NPM), size and the dividend payout ratio (DPR) not significant toward income smoothing practices. The result are -2Log Likelihood significantly 7.312 over than 2.776 affect the acceptance of model fit, Hosmer and Lemeshow’s Test significantly 0.771 over than 0.05 the acceptance of predicted model, Nagelkerke’s R Square 0.169, accurate model test 61.1% overall percentage companies to the acceptance of income smoothing.